Arctic sea ice radar freeboard from ERS-1, ERS-2, Envisat and CryoSat-2 ... - Bocquet, Marion; Fleury, Sara (Zenodo, 2023)
This dataset presents a radar freeboard time series from 1993 to 2021 for Arctic sea ice. Envisat, ERS-2 and ERS-1 radar freeboards have been estimated using CryoSat-2 as a reference, they are "SAR-like" estimations as they have been calibrated on CS-2 SAR TFMRA50 radar freeboard. ...